Single-stage functional reconstruction of the post-burn lower lip - Dhanraj, Prema; Kingsly, Paul M.; Lamba, Shashank; Shetty, Rahul; Petkar, Kiran S.; Sreekar, H. (European journal of plastic surgery, 2011)
Burn scar contracture of the lower face and neck is one of the most difficult subjects to solve because it produces problems with function and appearance. The lip is a part of the face that is frequently affected by burn injury. Lower lip deformity can be due to an extrinsic or intrinsic cause. Post-burn sequelae in this area results in cosmetic disfigurement and psychological trauma to patients as it is often associated with ectropion of the lower lip, severe microstomia leading to poor oral access for intubation, drooling, difficulty in eating, speaking and oral hygiene. The aim is to describe a single-stage correction to address all of these problems for a successful outcome. The technique was applied to 30 post-burn scar contractures of the lower lip. We classified the deformities of the lower lip and based on this classification the surgical procedure was executed to obtain functional improvement. At 2 months post-surgery the patient is able to demonstrate speech clarity with full functional oral range of movement. Neck release combined with vermillionectomy and comissuroplasty of the lip is a rational approach for preserving the function. A good planning of reconstructive procedures, facilitate patient recovery and optimize functional and aesthetic outcomes.